Нові напрямки розвитку сільськогосподарського машинобудування, заснованого на хвильових та віброхвильових принципах - Човнюк, Ю. В.; Дяченко, Л. А.; Chovniuk, Yuriy; Dyachenko, Lyubov (КНТУ, 2015)
Розглянуті нові напрямки розвитку машин сільськогосподарського призначення, які засновані на хвильових та віброхвильових принципах. У якості кількох ведучих вузлів таких машин можуть бути обрані мехатронні системи. The purpose of this study is to establish the parameters of the wave-like motion of low frequency of nonmetallic flexible working bodies, which is implemented by one of the following to wave formation. At the same latest based on the analysis of deformation waves on the surface of non-metallic flexible working bodies. New directions of development of machines for agricultural purposes, wich are based on the wave vibrationprinciples were considered. Mechatronic systems can be selected as several major sites such machines. During the formation of wave patterns (external and internal) they are held in the required movement and wave or waves, created by them, begin to move. During local deformation of non-metallic flexible working can be realized as constant movement and shape of the waves and create forms and variable wave motion with the help of management. In contrast to the rigid patterns in this method it is possible to reconstruct the process of formation of wave. The following methods of wave formation allow forming wave necessary forms,directions, parameters and durations on the non-metallic flexible working bodies of the technological machines for processing of agricultural raw materials. It allows for these machines to the different processes of processing of agricultural materials separately for each and collectively. The obtained results can be used to develop a new generation of structural classification of agricultural machinery from nonmetallic flexible working bodies that operate on the principles of vibration wave. The foregoing suggests the following: agricultural machinery non-metallic flexible working is a new class of the theory of machines and mechanisms and their characteristics are to objects mechatronics.
New directions of agricultural machinery based on the wave and vibo-wave principles
Keywords: нові напрямки; розвиток; сільськогосподарське машинобудування; хвилі; віброхвильові принципи; New directions; development; agricultural machinery; waves; vibro-wave principles